Quality Assessment of Soft Drinks Available at Local Market in Surkhet - Khadka, Promod; Sijapati, Lilaram; Regmi, Shukraraj; Thapa, Sushma; Basnet, Anup (KMC Journal, 2023)
Soft drinks have been reported to contain some toxic substance and other unwanted material beyond the acceptable limits in some countries including Nepal. Therefore, the main objective of this study was to access the quality and characteristics of selected soft drinks found in Birendranagar, Surkhet. Fifteen samples of marketed soft drinks were collected from the market. Qualitative test for the presence of reducing sugar, phosphates, alcohol and carbon dioxide in the samples were carried out. Quantitative test were also done for hardness, pH, iron content ammonia, chloride and also density measurement for ensuring the quality of available soft drinks. The presence of high sugar content in the sample and also the acidity of sample also indicate the presence of contaminants in the available sample. The pH value of Coca-Cola (2.5), highly acidic in nature, total hardness in Mountain Dew sample is found to be 350 mg/lit whereas for Pepsi is 76 mg/lit. Therefore, the quality of marketed soft drinks must be regulated by the regulatory bodies.